3,4,7-Trimethyl-2-(4-methylphenyl)-2H-pyrazolo[3,4-d]pyridazin-5-ium thiocyanate - Abdel-Aziz, H.A.; Bari, A.; Ng, S.W. (International Union of Crystallography, 2010)
1,1'-[5-Methyl-1-(4-methylphenyl)-1H-pyrazole-3,4-diyl)diethanone condenses with thiosemicarbazide in the presence of acetic acid to form the title salt, C15H17N4+center dot NCS-. The fused-ring system of the cation is almost planar (r.m.s. deviation = 0.020 angstrom) and the aromatic substituent is aligned at an angle of 48.2 (1)degrees with respect to the mean plane of the fused-ring system. The N atom at the 5-position is protonated and forms a N-H center dot center dot center dot N hydrogen bond to the thiocyanate cointer-ion.